MANAJEMEN PENGELOLAAN DANA HAJI PADA BADAN PENGELOLA KEUANGAN HAJI (BPKH) - Nur Rohmah Hidayati; Hilya Diniya; Mufrodah; Ria Anisatus Sholihah; Muhammad Taufiq Abadi (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
As Muslims, we are encouraged to carry out the Hajj pilgrimage in accordance with the fifth pillar of Islam. In Indonesia, the number of registrants for the Hajj pilgrimage continues to increase from year to year. Therefore, the Hajj Financial Management Agency (BPKH) was formed as an institution authorized to manage Hajj finances. The aim of this research is to explain the meaning, history, objectives and business activities of the Hajj Financial Management Agency, as well as the profile of the relevant institutions. This research method uses library research, namely by searching and collecting data from various sources. The results of this research are that the Hajj Financial Management Agency (BPKH) is an institution tasked with managing Hajj finances based on Law Article 20 Number 34 of 2014. The birth of BPKH was caused by irregularities in the Ministry of Religion, namely the management of Hajj finances which combined Hajj fund management and implementation. , then on July 26 2017 BPKH was officially established on the legal basis of Law Number 34 of 2014. The role of BPKH is to manage the Hajj economy which includes approval, guidance, expenditure and responsibility for the Hajj economy. BPKH has the right to obtain operational funds for the implementation of the Hajj Financial management program which is sourced from the value of the Hajj Financial benefits.